2017
DOI: 10.1093/nar/gkx458
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosome RNA Editing Mediator Complex proteins have distinct functions in gRNA utilization

Abstract: Uridine insertion/deletion RNA editing is an essential process in kinetoplastid parasites whereby mitochondrial mRNAs are modified through the specific insertion and deletion of uridines to generate functional open reading frames, many of which encode components of the mitochondrial respiratory chain. The roles of numerous non-enzymatic editing factors have remained opaque given the limitations of conventional methods to interrogate the order and mechanism by which editing progresses and thus roles of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
185
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(205 citation statements)
references
References 65 publications
19
185
1
Order By: Relevance
“…REMC is currently envisioned as comprised of TbRGG2, MRB8180, MRB800, MRB1860, and the redundant paralogs MRB8170/4160. It associates with GRBC in an RNA-enhanced manner, and appears to be more heterogeneous than GRBC Kafková et al 2012;Aphasizheva et al 2014;Simpson et al 2017). MRB10130, which contains domains that resemble Armadillo (ARM) or HEAT repeats, may play a role in organizing macromolecular interactions within RESC.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…REMC is currently envisioned as comprised of TbRGG2, MRB8180, MRB800, MRB1860, and the redundant paralogs MRB8170/4160. It associates with GRBC in an RNA-enhanced manner, and appears to be more heterogeneous than GRBC Kafková et al 2012;Aphasizheva et al 2014;Simpson et al 2017). MRB10130, which contains domains that resemble Armadillo (ARM) or HEAT repeats, may play a role in organizing macromolecular interactions within RESC.…”
Section: Introductionmentioning
confidence: 99%
“…GAP1/2 are the only proteins identified to date required for gRNA stabilization (Weng et al 2008;Hashimi et al 2009), while the remaining GRBC components appear to impact the initiation of RNA editing as indicated by an accumulation of pre-edited mRNA in cells depleted of these proteins (Weng et al 2008;Hashimi et al 2009;Ammerman et al 2011Ammerman et al , 2012Ammerman et al , 2013Aphasizheva et al 2014;Huang et al 2015). We recently used high-throughput sequencing analysis of partially edited transcripts in cells depleted of specific RESC components in combination with a novel bioinformatic platform, termed TREAT (trypanosome RNA editing alignment tool), to address RESC protein function (Simpson et al 2017). We demonstrated that mRNAs from cells depleted of GAP1 display both a defect in editing initiation as well as pausing in the 3 ′ to 5 ′ progression of editing consistent with a defect in gRNA exchange (Simpson et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations